Understanding How Behavioral Biases Shape Investment Decisions: The Mediating Effect of Emotional Intelligence - Ghimire, Dinesh Mani; Khanal, Ashok; Bhusal, Suresh; Adhikari, Madhav (Journal of Emerging Management Studies, 2025)
Purpose – This paper intends to investigate the impact of behavioral biases such as conservatism, overconfidence, regret, herding and anchoring on investment decisions of an individual capital market investor in Nepal. This paper also attempts to examine the mediating effect of emotional intelligence in the relationship between behavioral biases and investment decisions. Design/methodology/approach – This is a quantitative research approach. The research design employed for the study was cross-sectional including descriptive and causal. The data were collected with self-administered close ended structured questions. 299 investors from Lalitpur district of Nepal were surveyed using Google form. Data analysis was conducted through SPSS, and the mediating effect was conducted by using Hayes Process macro. Findings – The findings suggest that there is a significant effect of conservatism, overconfidence, and anchoring of Nepali investors on investment decision. However, herding and regret do not exhibit a significant impact on investment decisions. The study has also revealed that there is partial mediation effect of emotional intelligence in the relationship between behavioral biases and investment decisions. Implications – The research highlights the importance of investor education programs to mitigate behavioral biases and improve decision-making. Integrating emotional intelligence training into financial literacy initiatives can enhance investors’ ability to manage market complexities. Originality/value – This research stands out as one of the few studies to explore the role of emotional intelligence as a mediating variable in the relationship between behavioral biases and stock investment decisions, particularly within the context of Nepal. It offers a unique perspective on how emotional intelligence may influence decision-making processes influenced by biases, shedding light on a relatively unexplored area in Nepalese financial research.